Systematic review of behavior-related self-management assessment instruments for patients with diabetes - Jun Zhou; Yuanyuan Cui; Xingxin Cai; Mengqi Han; Wenxiu Wang; Peimin Liu; Jing Li; Guiying Guo (Frontiers in Public Health, 2026)
Objective To systematically evaluate the methodological quality and measurement properties of behavior-related self-management assessment instruments for patients with diabetes, and to provide evidence-based guidance for healthcare professionals when selecting appropriate assessment instruments. Methods A systematic literature search was conducted in CNKI, Wanfang Database, VIP Database, China Biomedical Literature Database (CBM), PubMed, Web of Science, Embase, and CINAHL to retrieve studies on behavior-related self-management assessment instruments for patients with diabetes. The search timeframe spanned from the inception of each database to December 15, 2025. Two independent researchers conducted literature screening and data extraction in accordance with predefined inclusion and exclusion criteria. The COSMIN guideline was used to evaluate the methodological quality of the included studies and the measurement properties of the included instruments and to formulate recommendation levels. Results A total of 14 studies involving 11 assessment instruments were included. No instrument met the criteria for a Grade A recommendation; 5 instruments were classified as Grade B and 6 as Grade C. Overall, the methodological quality and psychometric evidence base of the included instruments were limited. Content validity was frequently rated as indeterminate due to insufficient methodological reporting, while evidence for cross-cultural validity, measurement error, and responsiveness was largely absent. Among the included instruments, the SDSCA showed relatively stronger evidence for adults with type 2 diabetes mellitus, and the C-SMOD-A-23 showed relatively stronger evidence for adolescents with type 1 diabetes mellitus. However, both instruments were rated as Grade B and should therefore be used with caution rather than strongly recommended. Conclusion Evidence supporting the psychometric performance of diabetes self-management behavior scales is limited. While SDSCA and C-SMOD-A-23 could be used for select groups, their application requires caution due to unclear content validity and inadequate evidence of critical measurement properties. Future validations should follow COSMIN standards and prioritize content validity, cross-cultural validity, measurement error and responsiveness. Owing to absent age-specific validation data, existing tools’ suitability for older adults with diabetes—especially those with frailty, multimorbidity, cognitive dysfunction, functional/sensory impairment, polypharmacy and caregiver dependence—remains unclear and warrants targeted further research. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/view/CRD420251178394 , identifier: CRD420251178394.